Transfer matrix based reverse engineering approach to analyse annealing induced changes in optical transmission of TiO2/Ag/TiO2/Ag multilayer. (December 2021) - Jena, S.; Tokas, R.B.; Misal, J.S.; De, R.; Rao, K.D.; Thakur, S.; Udupa, D.V.
Highlights: TiO2 /Ag/TiO2 /Ag multilayer is prepared using asymmetric bipolar pulsed dc sputtering. Annealing induced changes in transmission spectrum of the multilayer is investigated. Reverse engineering of the spectrum is made to analyse and explain the observations. Three different multilayer models are executed for reverse engineering of the spectrum. Model suggests that interface roughness and absorption due to Ag varies with annealing. Abstract: Measured optical transmission spectrum of photonic structure comprising TiO2 /Ag/TiO2 /Ag multilayer is reverse engineered by employing transfer matrix method with three different multilayer models to analyse the factors responsible for the annealing induced changes in the transmission. The multilayer is made to have a single peak or a passband in the visible region, so that the spectral changes due to annealing can be observed more vividly. Prior to the multilayer deposition, single layer thin film of Ag and TiO2 are prepared using asymmetric bipolar pulsed dc sputtering and their optical constants such as refractive index and extinction co-efficient are determined. The multilayer is prepared by four-layer sequential deposition of Ag and TiO2 on BK7 glass substrate. The deposited TiO2 /Ag/TiO2 /Ag multilayer is annealed in the temperature range 100–300 °C. The optical transmission of the annealed multilayers is measured using spectrophotometer. The measured peak transmission and spectral bandwidth of the multilayer filter decreases with annealing, which is ascribed to inter-diffusion at the interfaces, and increasing absorption at the interfaces and in the silver layers of the multilayer. The ascription is resolved from the layers properties and interface parameters obtained by reverse engineering the measured transmission spectra. The rough interfaces in the multilayer are modeled as thin homogeneous layers following Bruggeman effective medium approximation, and the interface parameters are found to be varying with annealing.